2015
DOI: 10.1111/josh.12272
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive and Violent Behaviors in the School Environment Among a Nationally Representative Sample of Adolescent Youth

Abstract: Though some variation within demographic subgroups exists, rates of aggressive and violent behaviors in the context of the school environment continue to persist. Implications for the coordinated prevention of aggressive and violent behaviors among adolescent youth are discussed and recommendations for school-based prevention efforts are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
4
18
0
Order By: Relevance
“…The illustrative analysis showed that patterns not apparent by race/ethnicity comparisons were seen by including poverty in over half of the outcomes and our findings even suggested health-risk unintentional injury, sexual, and dietary behaviors had stronger associations with poverty than with race, which are in agreement with the findings of previous research. [5][6][7][12][13][14]23,38,39 Although employing Method FRPM as the proxy measure for individual-level poverty fails to account for racial/ethnic composition variations that exist within each school, the illustrative analysis confirmed that including at least some schoollevel poverty measure adds important information and analyses done without poverty are subject to biases and likely will not fully characterize risks.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The illustrative analysis showed that patterns not apparent by race/ethnicity comparisons were seen by including poverty in over half of the outcomes and our findings even suggested health-risk unintentional injury, sexual, and dietary behaviors had stronger associations with poverty than with race, which are in agreement with the findings of previous research. [5][6][7][12][13][14]23,38,39 Although employing Method FRPM as the proxy measure for individual-level poverty fails to account for racial/ethnic composition variations that exist within each school, the illustrative analysis confirmed that including at least some schoollevel poverty measure adds important information and analyses done without poverty are subject to biases and likely will not fully characterize risks.…”
Section: Discussionmentioning
confidence: 98%
“…26 This allows for analysis of local data as well as comparisons between jurisdictions and does not require individual student data. (9,16) .627 1 (0, 6) 6 (4,9) .002 Currently sexually active 40 (35,47) 25 (19,32) .004 50 (34, 66) 20 (16,24) .001 Ever been/gotten someone pregnant 9 (7, 11) 8 (5,11) .597 1 (0, 5) 4 (2, 7)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations